Effect of bromelain treatmant on chemical, microbiological and sensorial quality of pastramı - Yusuf Doğruer; Ümit Gürbüz; Mustafa Nizamlıoğiu; Suzan Yalçın; Mustafa Atasever (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the effect of bromelain treatment on chemical, microbiological and sensorial quality of pastrami. For this this purpose, different bromelain solutions (0,0.25,0.50 and 1.0 %) were used The significant differences were determined at the protein, pH and aw values after salting process, and at the SSP/Protein ratio and aw value before cemen treatment, and at the humidity of samples after cemen treatment. The only significant differences among the groups were the count of Staphylococcus-Micrococcus and Lactobacillus microorganisms which were determinated the salting process. In sensorial quality, the highest quality points were given the samples that were not applied bromelain solution. In conclution, it was determinated that bromelain treatment did not remarcable effect on chemical, microbiological and sensorial quality of pastrami.